Paper Retracted : The Effect Of Normal And Microwave Heating And Reheating Of Edible Oils On Their Biochemical And Biophysical Properties - Khedr, Yasser I.; Aboneima, Sahar E. (European Scientific Journal, ESJ, 2016)
Due to an authorship issue and on authors` demand the paper has been retracted by the ESJ editorial office. ESJ Editorial Office May 2016